Diagnostic assessment to identify learning styles and critical thinking in independent learning - Enita Sari; Evi Suryawati; Imam Mahadi (University of Muhammadiyah Malang, 2024)
Diagnostic assessment is a crucial step in the differentiated learning process as an implementation of the Merdeka curriculum. This study aimed to develop a diagnostic assessment instrument that can identify students' learning styles and critical thinking skills, especially in the Cell and Bioprocess material, in the context of implementing the Independent Curriculum. This study uses the Research and Development (R&D) method with the Borg and Gall development model. The subjects of the study were 35 grade X students of SMA Negeri 8 Pekanbaru who were selected randomly. Data analysis was carried out using the Rasch model with Winstep. The results of the study showed that the critical thinking diagnostic instrument had high validity and good reliability, while the learning style instrument had low reliability and needed further improvement. Several learning style assessment items were considered invalid and had to be adjusted or discarded. This diagnostic assessment instrument is expected to help teachers develop more effective learning strategies that are in accordance with the individual needs of students, so that it can improve the quality of learning, especially in understanding the Cell and Bioprocess material.